Potential Role of Oxidative Stress-Induced Apoptosis in Mediating Chromosomal Rearrangements in Nasopharyngeal Carcinoma - Tan, Sang-Nee; Sim, Sai-Peng; Khoo, Alan S.B. (Biomed Central, 2016)
Abstract Background Genetic aberrations have been identified in nasopharyngeal carcinoma (NPC), however, the underlying mechanism remains elusive. There are increasing evidences that the apoptotic nuclease caspase-activated deoxyribonuclease (CAD) is one of the players leading to translocation in leukemia. Oxidative stress, which has been strongly implicated in carcinogenesis, is a potent apoptotic inducer. Most of the NPC etiological factors are known to induce oxidative stress. Although apoptosis is a cell death process, cells possess the potential to survive apoptosis upon DNA repair. Eventually, the surviving cells may carry rearranged chromosomes. We hypothesized that oxidative stress-induced apoptosis may cause chromosomal breaks mediated by CAD. Upon erroneous DNA repair, cells that survive apoptosis may harbor chromosomal rearrangements contributing to NPC pathogenesis. This study focused on the AF9 gene at 9p22, a common deletion region in NPC. We aimed to propose a possible model for molecular mechanism underlying the chromosomal rearrangements in NPC. Results In the present study, we showed that hydrogen peroxide (H2O2) induced apoptosis in NPC (HK1) and normal nasopharyngeal epithelial (NP69) cells, as evaluated by flow cytometric analyses. Activity of caspases 3/7 was detected in H2O2-treated cells. This activity was inhibited by caspase inhibitor (CI). By nested Inverse Polymerase Chain Reaction (IPCR), we demonstrated that oxidative stress-induced apoptosis in HK1 and NP69 cells resulted in cleavages within the breakpoint cluster region (BCR) of the AF9 gene. The gene cleavage frequency detected in the H2O2-treated cells was found to be significantly higher than untreated control. We further found that treatment with CI, which indirectly inhibits CAD, significantly reduced the chromosomal breaks in H2O2-cotreated cells. Intriguingly, a few breakpoints were mapped within the AF9 region that was previously reported to translocate with the mixed lineage leukemia (MLL) gene in acute lymphoblastic leukemia (ALL) patient. Conclusions In conclusion, our findings suggested that oxidative stress-induced apoptosis could be one of the mechanisms underlying the chromosomal rearrangements in NPC. CAD may play an important role in chromosomal cleavages mediated by oxidative stress-induced apoptosis. A potential model for oxidative stress-induced apoptosis mediating chromosomal rearrangements in NPC is proposed.